Analisis Pengelolaan Arsip Dengan Menggunakan Google Spreadsheet Pada Subbag Tata Usaha Unit Kepatuhan Intern, Dirtjen Sumber Daya Air, Kementerian Pekerjaan Umum - Aisya Fajri Salsabila; Henry Eryanto; Muhammad Ikhwan (CV. ITTC INDONESIA, 2026)
The use of Google Spreadsheet in archive management at the Administrative Subdivision of the Internal Compliance Unit, Directorate General of Water Resources, Ministry of Public Works, is motivated by the incomplete implementation of an official electronic records management system at the unit level. As a result, archive management is still conducted in a semi-digital manner by utilizing simple and easily accessible applications as backups for physical and written records. This study aims to examine the archive management process using Google Spreadsheet, identify the challenges encountered, and analyze data security aspects in its implementation. This research employed a qualitative method with a case study approach. Data were collected through observation, interviews, and documentation, while data analysis was carried out through data reduction, data presentation, and conclusion drawing. The findings indicate that Google Spreadsheet is used as a medium for recording dynamic archives, which helps improve the efficiency of archive retrieval and facilitates online data access. However, several challenges remain, including limited application features, the risk of data duplication, dependence on internet connectivity, and insufficient control over access rights that may affect archive security.